Minimally Invasive Technique in the Management of Tibial Pilon Fractures: New Approach and Promising Results - Yassine Ben Bouzid; Rida-Allah Bassir; Monsef Boufettal; Jalal Mekkaoui; Mohamed Kharmaz; Moulay Omar Lamrani; Mohamed Saleh Berrada (Advances in Orthopedics)
Background. Comminuted tibial pilon fractures are induced by high-energy mechanisms and are often associated with soft tissue injuries. Their surgical approach is problematic due to postoperative complications. Minimally invasive management of these fractures has a considerable advantage in preserving the soft tissue and the fracture hematoma. Materials and Methods. We conducted a retrospective study of a series of 28 cases treated at the Orthopedic and Traumatological Surgery Department of the CHU Ibn Sina in Rabat over a period of 3 years and 9 months, from January 2018 to September 2022. Results. After a mean follow-up of 16 months, 26 cases had good clinical results according to the Biga SOFCOT criteria and 24 cases had good radiological results according to the Ovadia and Beals criteria. No cases of osteoarthritis were observed. No skin complications were reported. Conclusion. This study highlights a new approach that deserves to be considered for this type of fracture as long as no consensus has been given.